The Dutch house : a novel - Patchett, Ann (Harper, an imprint of HarperCollinsPublishers, 2019)
"Ann Patchett, the New York Times bestselling author of Commonwealth and State of Wonder, returns with her most powerful novel to date: a richly moving story that explores the indelible bond between two siblings, the house of their childhood, and a past that will not let them go"--